2018
DOI: 10.3844/sgamrsp.2018.135.154
|View full text |Cite
|
Sign up to set email alerts
|

Key Structural Aspects for Adaptive Facades - Activity Progress from the EU-COST Action TU1403 ‘Structural’ Task Group

Abstract: This open access article is distributed under a Creative Commons Attribution (CC-BY) 3.0 license.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…First examples of structural use of thin glass are the 11 m long FIFA World Cup 2014 players' bench and the lightweight retractable canopy developed by Neugebauer and collaborators (Neugebauer, 2015;Neugebauer et al, 2018), an excellent demonstrator for the potential that lies in the utilization of thin glass in movable structures. Recently, several authors have proposed the use of thin glass for the construction of kinetic and adaptive elements and façades (Topçu, 2017;Silveira et al, 2018), where this material allows to obtain the large deformations and movements required to maintain a dynamic optimum in performances with regard to energy, climate and comfort-related aspects (Bedon et al, 2018).…”
Section: Thin Glass As a Structural Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…First examples of structural use of thin glass are the 11 m long FIFA World Cup 2014 players' bench and the lightweight retractable canopy developed by Neugebauer and collaborators (Neugebauer, 2015;Neugebauer et al, 2018), an excellent demonstrator for the potential that lies in the utilization of thin glass in movable structures. Recently, several authors have proposed the use of thin glass for the construction of kinetic and adaptive elements and façades (Topçu, 2017;Silveira et al, 2018), where this material allows to obtain the large deformations and movements required to maintain a dynamic optimum in performances with regard to energy, climate and comfort-related aspects (Bedon et al, 2018).…”
Section: Thin Glass As a Structural Materialsmentioning
confidence: 99%
“…The architecture is now moving towards adaptive structures, i.e., kinetic structures equipped with a monitoring system to detect external/internal changes, whose information are used by a control system determining the behavior of actuators capable of changing geometry or other structural characteristics. This kind of structure is able to modify its "functions, features or behavior over time in response to transient performance requirements and boundary conditions, with the aim of improving the overall building performance" (Morales-Beltran and Teuffel, 2013;Loonen et al, 2017;Bedon et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, several authors have suggested to better exploit its high deformability by cold bending it, to gain structural stiffness in static use in curved design or membrane structures replacing the expensive process of bending glass at high temperatures . Furthermore, it is suitable to be used in kinematic or adaptive designs (Topçu 2017;Silveira et al 2018;Bedon et al 2018), where its high flexibility allows for changes in orientation and position by bending the elements, avoiding the use of hinges in systems of foldable rigid panels. This has suggested its use for structures suitable for strong modification of shape and openings, as stadium roofs, lightweight retractable canopies (Neugebauer 2015) and movable greenhouses (Galuppi 2018;D'Ambrosio and Galuppi 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Next generation of building enclosures are complex adaptive systems combining high-tech components and latest technology achievements. This might involve the use of smart materials and kinematic mechanisms, which make them able to respond to transient loading and boundary conditions in order to improve the overall building performance (see for example [1][2][3]). Although current numerical tools allow for extensive investigation of the structural performance of adaptive facades at different levels, as also discussed in [1], the ultimate verification of performance criteria required by building regulations and standards might involve dedicated experimental testing procedures.…”
Section: Introductionmentioning
confidence: 99%